(untitled) - Miller, Roger LeRoy (Mason, MN, 2007)
This book is truly a money & banking text of the 21st century. The authors combined a good writing style, one that is thorough yet succinct with a full coverage of the latest developments in money, banking and financial markets, along with the advent of information technology and global integration
Keywords: Banks and banking,Money,Financial institutions,Tổ chức tài chính,Ngân hàng và giao dịch ngân hàng